Kenya Economic Update, October 2016 : Beyond Resilience--Increasing Productivity of Public Investments - World Bank Group (World Bank, Nairobi, Kenya, 2016)
Kenya is one of the bright spots in Sub-Saharan Africa. With economic growth rates sustained at above 5 percent, Kenya has outperformed the regional average, for 8 consecutive years. Robust domestic demand emanating from private consumption and government investment are the key drivers of growth, underpinned by a stable macroeconomic environment, lower oil prices, diversification, improved security perceptions, and ongoing structural reforms. Medium term economic prospects for Kenya remain robust. Ongoing public infrastructure investments will continue to play a ‘crowding-in’ role, easing transport and energy costs, and supporting economic expansion in construction andindustry. Private consumption will drive service sector growth, while agricultural sector will remain largely dependent on favorable weather conditions and timely availability of inputs. Though oil prices are expected to pick-up over the forecast horizon, Kenya’s external sector account will remain healthy on account of a steady increase in remittances, a rebound in tourism and a rise in foreign direct Investment (FDI). Nonetheless, there exist downside risks that can dent future growth prospects. Risks to Kenya’s future growth prospects that are not included in our baseline outlook emanate from both external and domestic sources. On the external front, these include weaker than expected growth in the global economy, volatility in global financial markets and a spike in oil prices. On the domestic front, these include delays to fiscal consolidation, adverse weather developments, and potential uncertainties associated with the run-up to 2017 elections that could lead to a wait-and-see attitude by investors, thereby dampening short-term growth prospects.